2004
DOI: 10.1037/1076-898x.10.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Visual Estimation of Spatial Requirements for Locomotion in Novice Wheelchair Users.

Abstract: Locomotion using a wheelchair requires a wider space than does walking. Two experiments were conducted to test the ability of nonhandicapped adults to estimate the spatial requirements for wheelchair use. Participants judged from a distance whether doorlike apertures of various widths were passable or not passable. Experiment 1 showed that participants underestimated the spatial requirements for wheelchair use but overestimated the spatial requirements for walking. Experiment 2 showed that their underestimatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
93
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(102 citation statements)
references
References 34 publications
8
93
1
Order By: Relevance
“…Skilled wheelchair users showed an RPB of 1.02 from Flascher et al (1995) and 1.03 from Savelsbergh et al (1998). This confirms that walkers and skilled wheelchair users similarly judge and reduce risks, although skilled wheelchair users adopt a smaller safety margin (Higuchi et al, 2004).…”
Section: Introductionsupporting
confidence: 70%
See 3 more Smart Citations
“…Skilled wheelchair users showed an RPB of 1.02 from Flascher et al (1995) and 1.03 from Savelsbergh et al (1998). This confirms that walkers and skilled wheelchair users similarly judge and reduce risks, although skilled wheelchair users adopt a smaller safety margin (Higuchi et al, 2004).…”
Section: Introductionsupporting
confidence: 70%
“…The protocol was divided into five parts as suggested by Higuchi et al (2004). The practice group was subjected to (i) visual estimation of different apertures in the "walking" situation, (ii) familiarization with the wheelchair for 5 min, (iii) pre-practice visual estimation of different apertures in the "wheelchair" situation, (iv) motor practice with the wheelchair, passing through different apertures, and (v) postpractice visual estimation of different apertures in the "wheelchair" situation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…While this is possible in at least some cases, it does not explain cases in which participants overestimate their action capabilties. For example, research has shown that novice wheelchair users generally overestimated their ability to roll through an aperture (Higuchi, Takada, Matsuura, & Imanaka, 2004), and toddlers overestimated their ability to walk down slopes (Adolph, 2008). It is also does not explain cases in which perceivers underestimate their ability to perform a behavior that poses little or no accident or injury risk (e.g., overhead reaching while standing on the floor; Wagman & Morgan, 2010).…”
mentioning
confidence: 99%